Phase I study design for non-cytotoxic agents - Parulekar, Wendy (Henry Stewart Talks, 2009)
Phase I study development: role in clinical drug development, Terminology, Phase I study objectives, Preclinical data requirements, Efficacy, Target modulation, Toxicity, PK checklist, Phase I study conduct, Determination of the RPTD, Cytotoxic agent, Patient population, Starting dose, Dose escalation, Dose escalation methods, Phase I study design for non-cytotoxic agents, Challenges for the evaluation of non-cytotoxic agents, Two approaches to study phase I study design driven by target effects, General considerations for RPTD determination, Clinical trial sample analyses, Examples: Cetuximab, Erlotinib, O6-Benzylguanine, Phase I review, Agents/targets, Recommended phase II dose and primary basis
Archived at 2021/02/25